Are Malaysian exports and imports cointegrated? A comment - Tang, Tuck Cheong (Sunway University College, 2005)
This commentary aims to provide an insight on the work by Choong, Soo and Zulkornain Yusop (2004), which appeared in the inaugural issue of this journal. The study has found a long-run relationship (cointegration) between Malaysian imports and exports for the annual period 1959?2000. An empirical illustration in this commentary reveals that a cointegration between Malaysian exports and imports as documented by CSZ requires further investigation before it can be generalized.